Characteristics and clinical outcomes of patients with ALK‐positive anaplastic large cell lymphoma: Report from the prospective international T‐cell lymphoma project. Issue 5 (15th September 2022) - Chiattone, Carlos; Civallero, Monica; Fischer, Thais; Miranda, Eliana; Manni, Martina; Zing, Natalia P. C.; Pileri, Stefano A.; Montoto, Silvia; Horwitz, Steven M.; Cabrera, Maria Elena; De Souza, Carmino A.; Nagler, Arnon; et al.
Abstract: The T‐cell Lymphoma Project is an international registry prospective study that enrolled patients with newly diagnosed peripheral T‐cell and NK‐cell lymphomas (PTCL). The main objective was to define the clinical features and outcomes, establishing a robust benchmark for future clinical trials. Seventy‐four institutions from 14 countries in North America, South America, Europe, and Asia collected data on patients diagnosed and treated at their respective centers between September 2006 and February 2018. Among 1553 PTCL patients, 131 (8.4% of the total cohort) were confirmed to have anaplastic large cell lymphoma ‐ kinase positive (ALCL, ALK+). The median age of the patients was 39 years (18–84). Sixty‐five patients (66%) had advanced‐stage disease, although majority (45 patients, 54%) had a low‐risk International Prognostic Index (IPI) score (0–1). Of 97 patients treated with chemotherapy, 97% received anthracycline‐containing regimens. The overall response rate was 81%, with 69 patients (70%) achieving complete remission. Estimated OS and PFS at 3 years were 77% (95% CI: 54%–99%) and 68% (95% CI: 46%–90%), respectively, and at 5 years were very similar, 77% of OS (95% CI: 62%–92%) and 64% of PFS (95% CI: 34%–94%). Multivariate analysis for PFS showed advanced stage (hazard ratios [HR]: 4.72, 95% CI: 1.43–23.9, p  = 0.015), elevated lactate dehidrogenade (LDH) (HR 4.85; 95% CI: 1.73–13.60, p  = 0.001), and Eastern Cooperative Oncology Group Performance Status scale (ECOG‐PS) ≥2 (HR: 5.25; 95% CI: 1.68–16.4, p  = 0.024). For OS, elevated LDH (HR: 3.77; 95% CI: 1.98–14.17, p  = 0.014) and ECOG‐PS ≥2 (HR: 4.59; 95% CI: 1.46–14.39, p  = 0.004) were identified. In summary, although the outcome of ALK+ ALCL is superior to that of other PTCLs, it remains sufficiently favorable, given the young median age of the patients. Our results confirm the usefulness of both IPI and Prognostic Index for T‐cell Lymphoma (PIT) in identifying groups of patients with different outcomes. Clinical Trials ID: NCT01142674.